Virus-encoded microRNAs - Grundhoff, Adam; Sullivan, Christopher S. (Virology (New York, N.Y.), 2011)
MicroRNAs (miRNAs) are the subject of enormous interest. They are small non-coding RNAs that play a regulatory role in numerous and diverse cellular processes such as immune function, apoptosis and tumorigenesis. Several virus families have been shown to encode miRNAs, and an appreciation for their roles in the viral infectious cycle continues to grow. Despite the identification of numerous (>225) viral miRNAs, an in depth functional understanding of most virus-encoded miRNAs is lacking. Here we focus on a few viral miRNAs with well-defined functions. We use these examples to extrapolate general themes of viral miRNA activities including autoregulation of viral gene expression, avoidance of host defenses, and a likely important role in maintaining latent and persistent infections. We hypothesize that although the molecular mechanisms and machinery are similar, the majority of viral miRNAs may utilize a target strategy that differs from host miRNAs. That is, many viral miRNAs may have evolved to regulate viral-encoded transcripts or networks of host genes that are unique to viral miRNAs. Included in this latter category is a likely abundant class of viral miRNAs that may regulate only one or a few principal host genes. Key steps forward for the field are discussed, including the need for additional functional studies that utilize surgical viral miRNA mutants combined with relevant models of infection.